Cerebellar Ataxia, Opsoclonus, and Neuroblastoma - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
A 20 month-old girl with cerebellar ataxia and opsoclonus associated with neuroblastoma is reported from the Pediatric Neurology Unit, Tel Aviv Medical Center, Israel.